MORPHOLOGICAL VARIATION IN HEMIGORDIUS HARLTONI CUSHMAN & WATERS, 1928: REMARKS ON THE TAXONOMY OF CARBONIFEROUSAND PERMIAN HEMIGORDIOPSIDS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
Nine morphotypes recognized within its population suggest that Hemigordius harltoni is a polytypic species. Narrowly discoidal to discoidal morphotypes are dominant in the population whereas lenticular ones are rare and sporadic. The degree of morphological variation in H. harltoni prompts us to question the validity of several previously named Carboniferous and Permian taxa. The definition of these taxa, generally based on few specimens, is far from being satisfactory to describe the intraspecific variability. Some named species are actually morphotypes belonging to highly variable species.